Single incision laparoscopic abdominal surgeries: case series of 155 various procedures, an observational cohort study - Özkurt, Enver (Turk J Surg, 2020)
OBJECTIVES: Over the last decade, surgeons have started to think of the ways in which to further reduce the trauma of surgery and improve cosmesis. Consequently, many surgeons have yielded to single incision laparoscopic surgeries (SILS) in order to maximize operative and postoperative outcomes. This study aimed to highlight the feasibility and challenges of different procedures by presenting our data about different fields of abdominal SILS practices with long term follow-up. MATERIAL AND METHODS: We retrospectively analysed an observational cohort of 155 patients who underwent surgery for different indications using the SILS technique. RESULTS: Of the 155 SILS procedures: 75 (48.4%) were cholecystectomies; 22 (14.2%) were splenectomies; 17 (11%) were hernia repairs; 11 (7.1%) were appendectomies; 8 (5.2%) were partial colon resections; 8 (5.2%) were adrenalectomies; 6 (3.8%) were distal pancreatectomy & splenectomies; 3 (1.9%) were subtotal gastrectomies; 3 (1.9%) were partial liver resections; and 2 (1.3%) were Nissen fundoplications. Ten (6.5%) early and 3 (1.9%) late postoperative complications were detected. No mortality or late morbidity (> 30 days) was detected due to SILS procedures. CONCLUSION: SILS is a feasible technique in experienced hands for specific procedures. Meticulous patient selection is also important for good cosmetic results and outcomes.